Exploring the Trade-Environment Linkage: A Bibliometric Investigation of Trade Openness and Carbon Emissions - Poh, Paik Xuan; Chin, Lee; Kaliappan, Shivee Ranjanee; Mazlan, Nur Syazwani (Advances in Social Sciences Research Journal, 2025)
The relationship between trade openness (TO) and carbon emissions (CE) has taken center stage in environmental economics. However, the ultimate impact of TO on CE relies on the relevant scale, technique, and composition of TO. Hence, this study conducted a bibliometric analysis on 999 documents retrieved from the Scopus database, which spans from 2005 to 2024. Furthermore, this paper carried out a performance and science mapping analysis using the Excel-based tool biblioMagika, as well as OpenRefine and VOSviewer software. The study focuses on understanding the research landscape and the results indicate that there is an increasing publication trend in the TO and CE domain. The study identifies Kirikkaleli Dervis from Cyprus as the most pertinent author in this field by evaluating different metrics. Besides that, the co-occurrence analysis shows the five main clusters comprising environmental sustainability, policy modelling, climate change, regional studies, and economic growth and energy policies. Also, future research should focus on merging trade policy with climate change initiatives, examining the role of digital trade, and investigating the heterogeneous effect of TO on CE across different economic sectors and regions. Therefore, this study's findings will shed light on previous research and suggest direction for future studies.